2008
DOI: 10.1002/anie.200802516
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Thiol–Ene Coupling as a Click Process for Materials and Bioorganic Chemistry

Abstract: The century‐old thiol–ene radical reaction is now being recognized among the ranks of other click‐type reactions (see scheme). Recent applications in dendrimer and glycopeptide syntheses demonstrate the efficiency of this process for the assembly of complex molecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
422
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(427 citation statements)
references
References 42 publications
0
422
0
5
Order By: Relevance
“…After successful discovery of click chemistry concept by Sharpless and Meldal, it is easy to perform polymer modification with high yield under mild conditions, such as rapid, stereospecific, orthogonal and no by-product coherent with the green chemistry [26]. Today, a series of reactions including Huisgen type Cu(I) catalyzed cycloaddition (CuAAC) [27,28], thiol-ene [29][30][31] and Diels-Alder [32] are recognized as well-known click chemistry reactions [33]. Modification of polymers with CuAAC click reaction is very general, robust and particularly simple compared to other click chemistry reactions [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…After successful discovery of click chemistry concept by Sharpless and Meldal, it is easy to perform polymer modification with high yield under mild conditions, such as rapid, stereospecific, orthogonal and no by-product coherent with the green chemistry [26]. Today, a series of reactions including Huisgen type Cu(I) catalyzed cycloaddition (CuAAC) [27,28], thiol-ene [29][30][31] and Diels-Alder [32] are recognized as well-known click chemistry reactions [33]. Modification of polymers with CuAAC click reaction is very general, robust and particularly simple compared to other click chemistry reactions [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Today, thiol-ene additions (or thiol-ene click reactions) are considered as a versatile and broadly applicable tool in polymer science. [18] Nevertheless, already early on it was discovered that dithiols and dienes are suitable monomers for polymer synthesis. [19] More recent investigations have shown that quite high molecular weight polythioethers can be obtained in that way, [20] that initiators are not necessary for the reaction to proceed, [21] but radical inhibitors suppress the polymerization for some time.…”
Section: Introductionmentioning
confidence: 99%
“…The thiol-ene click reaction has proven to be a versatile tool in organic synthesis. [12][13][14][15] In particular, such a strong nucleophilic character has been used in the thiol-Michael reaction which is exploited extensively in synthesis and polymer modification since it leads to thioesters in very high yields. 16,17 Hence, in order to verify the nucleophilicity of compound 4, it was reacted in the presence of two acrylates as shown in scheme 2.…”
Section: Resultsmentioning
confidence: 99%